DIABETES DURATION AND RETINAL NERVE FIBER LAYER THICKNESS RELATED DEGREE OF DIABETIC RETINOPATHY: Oral Presentation - Observational Study - Resident - Nadia, Felanda Ahsanu; Sari, Masitha Dewi; Delfi (Ophthalmologica Indonesiana, 2024)
Introduction & Objectives Diabetic retinopathy is an ocular complication of diabetes mellitus (DM). Several studies have shown that neurodegenerative changes in the retina occur earlier than microvascular changes. Measurement of retinal nerve fiber layer thickness can detect neurodegeneration at an early stage. This study aims to analyze the relationship of diabetes duration and retinal nerve fiber layer thickness with degree of diabetic retinopathy in type 2 diabetes mellitus patients. Methods This research was analytic observational research with cross-sectional design. The sample was type 2 diabetes mellitus patients with diabetic retinopathy who visited the eye clinic at the University of Sumatera Utara General Hospital. The sample were then analyzed with the Kruskal Wallis test to find relationship of diabetes duration and retinal nerve fiber layer thickness with degree of diabetic retinopathy in type 2 diabetes mellitus patients. Results The sample of this study were 20 subjects with diabetic retinopathy and 20 subjects without diabetic retinopathy as the control group. The mean duration of having DM in the group of patients with mild NPDR was 5.33 years, with moderate NPDR was 9.13 years and with PDR was 15.33 years. Using the Kruskal Wallis test revealed that there was no significant relationship between degree of diabetic retinopathy with Avg RNFL (p=0.495), superior RNFL (p=0.385), inferior RNFL (p=0.111), temporal RNFL (p=0.064), nasal RNFL (p=0.535). Conclusion There was a significant difference between diabetes duration with degree of diabetic retinopathy but no significant between retinal nerve fiber layer thickness with degree of diabetic retinopathy.